Dengue encephalitis - Amit A Bharadiya; Jyotsna B Jaju; Swati C Aundhakar; Makarand Mane; Vikrant Mahajani (Wolters Kluwer Medknow Publications, 2015)
Presentation of dengue fever can range from asymptomatic infection to life-threatening dengue hemorrhagic fever and dengue shock syndrome. We report a case of dengue fever presenting as encephalitis, which is very rare.